Taxing mechanisms on salty foods: investigation of effectiveness through price elasticity and cross price elasticity of demand - Vahid Yazdi-Feyzabadi; Mohammad Hajizadeh; Enayatollah Homaie Rad; Anita Reihanian; Ali Hussein Samadi; Marjan Mahdaviroshan (Journal of Health, Population and Nutrition)
Abstract Background Salt consumption control strategies can help to decrease hypertension and related cardiovascular diseases. Taxation mechanisms help to reduce the utilization of harmful commodities like salts. This study aims to analyze the impact of taxing salty foods on salt intake in Iran by examining the price elasticity of demand (PED) and cross-price elasticity of demand (XED) for salty foods. Methods This study used 38,328 household-level data from the 2019 Iranian Household Income and Expenditures Survey. This PED and XED for salty foods were calculated, and changes in household salt consumption due to salt taxation were estimated using a mathematical simulation method. Results The findings revealed that the PEDs for noodles and pilaffs (− 4.89) and bread (− 2.03) are higher than that for other commodities. Noodles and salt (− 4.55) and breads and salt (− 1.61) exhibited the highest XED. Following 20% taxation, total salt intake is projected to increase by approximately 125 g per month. Conclusion Taxing mechanisms are ineffective in reducing the consumption of salty foods. Instead of reducing salt intake, households tend to shift to lower-quality, cheaper salty foods after the tax are implemented. However, these mechanisms can be used for increasing the government revenue.